Mycoplasma Pneumoniae Post-encephalitic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Chang Gung Children's and Memorial Hospitals, Taoyuan, Taiwan, investigated the clinical manifestations, laboratory, EEG, and neuroimaging features of M pneumoniae-related encephalitis and its prognosis.